Writing Self-Efficacy among EFL Students: The Role of Teachers’ Motivational Practices in Indonesian Higher Education - Muh Tahir; Munir; Umi Nurul Fahri (Universitas Islam Negeri Palopo, 2025)
This study investigates how English lecturers' motivational strategies influence students' self-efficacy in academic writing. Employing a sequential exploratory mixed-methods design (QUAL → quan), the research consisted of two phases: a qualitative inquiry involving semi-structured interviews with three lecturers, followed by a quantitative survey distributed to 30 undergraduate EFL students. The qualitative findings revealed the implementation of motivational practices such as goal-setting, scaffolding, autonomy support, reinforcement, constructive feedback, and classroom climate. Students perceived these strategies as fostering greater writing confidence. A simple linear regression analysis confirmed a significant positive influence of teacher motivational strategies on students' writing self-efficacy (R = 0.511, R² = 0.261, B = 0.320, p = 0.004). These results underscore the pedagogical importance of strategically designed motivational interventions in enhancing EFL learners' self-belief and performance in academic writing. The study highlights the need for professional development programs to equip educators with evidence-based motivational teaching tools.